Novel EDA mutation in X‐linked hypohidrotic ectodermal dysplasia and genotype–phenotype correlation. (24th October 2015) - Zeng, B; Lu, H; Xiao, X; Zhou, L; Lu, J; Zhu, L; Yu, D; Zhao, W
Abstract : Objectives: X‐linked hypohidrotic ectodermal dysplasia (XLHED) is characterized by abnormalities of hair, teeth, and sweat glands, while non‐syndromic hypodontia (NSH) affects only teeth. Mutations in Ectodysplasin A ( EDA ) underlie both XLHED and NSH. This study investigated the genetic causes of six hypohidrotic ectodermal dysplasia (HED) patients and genotype–phenotype correlation. Methods: The EDA gene of six patients with HED was sequenced. Bioinformatics analysis and structural modeling for the mutations were performed. The records of 134 patients with XLHED and EDA ‐related NSH regarding numbers of missing permanent teeth from this study and 20 articles were reviewed. Nonparametric tests were used to analyze genotype–phenotype correlations. Results: In four of the six patients, we identified a novel mutation c.852T>G (p.Phe284Leu) and three reported mutations: c.467G>A (p.Arg156His), c.776C>A (p.Ala259Glu), and c.871G>A (p.Gly291Arg). They were predicted to be pathogenic by bioinformatics analysis and structural modeling. Genotype–phenotype correlation analysis revealed that truncating mutations were associated with more missing teeth. Missense mutations and the mutations affecting the TNF homology domain were correlated with fewer missing teeth. Conclusions: This study extended the mutation spectrum of XLHED and revealed the relationship between genotype and the number of missing permanent teeth.